Review on Bandung Transportation Plan Policy - Tonny Judiantono (Journal of Architecture, Planning and Construction Management, 2020)
ransportation service is a derive demand, it means a demand what it need to reach a specific aim. Cause of that, the basic step on the transportation system planning should follow these steps: Formulation of goals and objectives, Data collection, Analytical methods, Forecasting, Formulation of alternative plans, Evaluation and Implementation. The Sustainability of a transportation system has to consider: The transportation existing condition, financial condition, people opinion, government policies, social-economics constraint, and the physical condition of that area. By comparative method between Bandung transportation problems and the strategic plan of the Bandung transportation system which has written on the RTRW (Masterplan) of Bandung 2010-2030, can be concluded that transportation system plan policy has not clear as an explicit plan which it need by the city of Bandung, cause it is not fully following the basic steps of transportation system planning and did not looked to the constraint of the transportation system plan. We recomendate to compose the transportation system plan as derivate, which more clear the criteria and target aims.